Seasonal infestation patterns of ticks on Hokkaido sika deer ( Cervus nippon yesoensis ) - Shimizu, Kotaro; Shimozuru, Michito; Yamanaka, Masami; Ito, Genta; Nakao, Ryo; Tsubota, Toshio (Parasitology, 2024)
Ticks prefer specific feeding sites on a host that are influenced by host–tick and tick–tick interactions. This study focused on the spatiotemporal distribution of ticks in Hokkaido sika deer, an important tick host in Hokkaido, Japan. Tick sampling was performed on the sika deer in the Shiretoko National Park between June and October 2022. Ticks were collected from 9 different body parts of the deer to compare their attachment site preferences. Interspecific and intraspecific relationships among ticks were examined using co-occurrence analysis. The collected ticks were nymphal and adult stages of 4 species: Ixodes ovatus , Ixodes persulcatus , Haemaphysalis japonica and Haemaphysalis megaspinosa . Seasonal variations in tick burden were observed, with I. persulcatus and I. ovatus peaking in June and declining towards October; H. japonica showing low numbers in July and August and increasing from September; and H. megaspinosa appearing from September onwards with little variation. Attachment site preferences varied among species, with a significant preference for the pinna in I. ovatus and I. persulcatus . Haemaphysalis japonica was mainly found on the body and legs between June and August, and shifted to the pinna from September. Haemaphysalis megaspinosa showed a general preference for areas other than the legs. Co-occurrence analysis revealed positive, negative and random co-occurrence patterns among the tick species. Ticks of the same genus and species exhibited positive co-occurrence patterns; I. ovatus showed negative co-occurrence patterns with Haemaphysalis spp. This study revealed the unique attachment site preferences and distinct seasonal distributions of tick species in the Hokkaido sika deer.